SISTEM PAKAR PENDETEKSI KERUSAKAN MOTOR MATIK PADA PT. MEGA WAHANA PESONA SENGETI: Expert system, Artificial Intelligence, Motorbike demage. - Puad, Lailyn (JURNAL AKADEMIKA, 2018)
Expert system is a computer based system using knowledge, fact, and logical technique in solving a problem which usually can be solve by the expert in a certain field. This expert system has dynamic characteristic, It means the user who has access right as expert is able to manage knowledge along with the development of recent knowledge. This expert system can help motorbike owner and mechanical fledgeling ones. Here in word pictures about damage which happens, analysing trouble, with damage and solution cause that is expoused draws so get to work righteously an expert or its pro, without remove dependency on a n expert.